2013
DOI: 10.1096/fj.13-231852
|View full text |Cite
|
Sign up to set email alerts
|

Maternal‐fetal transfer of selenium in the mouse

Abstract: Selenoprotein P (Sepp1) is taken up by receptor-mediated endocytosis for its selenium. The other extracellular selenoprotein, glutathione peroxidase-3 (Gpx3), has not been shown to transport selenium. Mice with genetic alterations of Sepp1, the Sepp1 receptors apolipoprotein E receptor-2 (apoER2) and megalin, and Gpx3 were used to investigate maternal-fetal selenium transfer. Immunocytochemistry (ICC) showed receptor-independent uptake of Sepp1 and Gpx3 in the same vesicles of d-13 visceral yolk sac cells, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 23 publications
2
97
0
9
Order By: Relevance
“…It would be important to test in future studies whether other members of the lipoprotein receptor family may also function in SelP uptake and contribute to the hierarchical retention of Se by different tissues. It should also be noted that, in addition to the receptor-dependent transport of SelP, this selenoprotein can be taken up by cells nonspecifically through pinocytosis (37). But this uptake mechanism appears to function mostly under Se-adequate conditions.…”
Section: Selenoprotein Pmentioning
confidence: 99%
“…It would be important to test in future studies whether other members of the lipoprotein receptor family may also function in SelP uptake and contribute to the hierarchical retention of Se by different tissues. It should also be noted that, in addition to the receptor-dependent transport of SelP, this selenoprotein can be taken up by cells nonspecifically through pinocytosis (37). But this uptake mechanism appears to function mostly under Se-adequate conditions.…”
Section: Selenoprotein Pmentioning
confidence: 99%
“…Bone marrow, which exports blood cells containing selenoproteins, and the placenta, which takes up Sepp1 from the maternal circulation to supply selenium to the fetus (20), both express relatively large amounts. Brain, muscle, and other tissues express moderate amounts.…”
Section: Apoer2-mediated Uptake Of Sepp1 From the Systemic Circulationmentioning
confidence: 99%
“…Moreover, apoER2 À/À mice had no SelP in BCECs or choroid plexus cells at the BBB, suggesting a key role of ApoER2 in brain Se uptake, and also the presence of an unknown redundancy mechanism for Se transport. It remains unclear if other members of the lipoprotein receptor family may participate of SelP uptake, since Burk et al 47 observed an alternative mechanism that does not appear to depend directly on selenoproteins participating on the transfer of Se from pregnant dam to the fetus, and it is unclear if this mechanism is conserved in the postnatal period.…”
Section: Selenoprotein P and Brain Selenium Hierarchymentioning
confidence: 99%